Drawing Safety Right Out of the Blue - Dow Chemical Company (1940)
Advertisement for Dowflake Calcium Chloride, a product of the Dow Chemical Company marketed for use to control dust on unpaved roads and parking lots, as well as a roadway deicer. The advertisement details the nuisance of dust arising from the use of motor cars and extols the benefits of using Dowflake as a surface treatment to lock in moisture and reduce the maintenance and upkeep required of unpaved gravel roads, as well as playgrounds, tennis courts, and other surfaces.
Keywords: Chemical industry; Dow Chemical Company; Corporations; Advertising; Dust control; Roads--Maintenance and repair; Calcium chloride